HUBUNGAN STATUS PEKERJAAN IBU DENGAN MOTIVASI PEMBERIAN ASI EKSKLUSIF DI WILAYAH KERJA PUSKESMAS MENGWI III KABUPATEN BADUNG - Ni Made Sri Ardhia Padmasari; Ida Arimurti Sanjiwani; I Made Suindrayasa (Coping: Community of Publishing in Nursing, 2020)
Exclusive breastfeeding is very important for baby's growth and development. In 2015, the coverage of exclusive breastfeeding in Bali Province still has not reached the expected target number. The motivation of a mother is crucial in giving exclusive breastfeeding for six months. One of the factors that influence the motivation of exclusive breastfeeding is the mother’s employment status. The purpose of this study was to determine the relationship between the employment status of mothers with the motivation of exclusive breastfeeding. This study was a correlative study with a cross-sectional approach. The sample consisted of 90 nursing mothers who had babies aged 0-6 months obtained by purposive sampling technique. Data collection was used a questionnaire. The chi-square test showed p value 0,003 (p < 0.05) which means that there was a relationship between the employment status of mothers with the motivation of exclusive breastfeeding. The results of this study is expected to be a picture for health workers to provide health promotion about the importance of exclusive breastfeeding and to improve community empowerment in an effort to increase the coverage of exclusive breastfeeding. Mothers is expected to actively seek information about exclusive breastfeeding so that the mother's motivation in giving exclusive breastfeeding increases.